A Retrospective Observation of Treatment Outcomes Using Decitabine-Combined Standard Conditioning Regimens Before Transplantation in Patients With Relapsed or Refractory Acute Myeloid Leukemia - Li, Yuhang; Cheng, Longcan; Xu, Chen; Chen, Jianlin; Hu, Jiangwei; Liu, Na; Lan, Sanchun; Xie, Jing; Sun, Ting; Wang, Lei; Zhang, Yu; Sun, Yao; et al. (Frontiers in Oncology, 2021)
Hypomethylating agents, decitabine (DAC) and azacitidine, can act as prophylactic and pre-emptive approaches after allogeneic hematopoietic stem cell transplantation (allo-HSCT) and a non-intensive bridging approach before allo-HSCT. However, they are rarely used as a part of conditioning regimens in patients with relapsed or refractory acute myeloid leukemia (AML). This retrospectively study included a total of 65 patients (median, 37; range, 13-63) with relapsed or refractory AML who were treated by allo-HSCT after myeloablative conditioning regimens without or with DAC (high-dose DAC schedule, 75 mg/m2 on day -9 and 50 mg/ m2 on day -8; low-dose DAC schedule, 25 mg/m2/d on day -10 to -8). DAC exerted no impact on hematopoietic reconstitution. However, patients, who were treated with the high-dose DAC schedule, had significantly higher incidence of overall survival (OS, 50.0%) and leukemia-free survival (LFS, 35.0%), as well as lower incidence of relapse (41.1%) and grade II-IV acute graft versus host disease (aGVHD, 10.0%) at three years, when compared with those treated with standard conditioning regimens or with the low-dose DAC schedule. In conclusion, high-dose DAC combined with standard conditioning regimens before allo-HSCT is feasible and efficient, and might improve outcomes of patients with relapsed or refractory AML, which provides a potential approach to treat these patients.